NILAI-NILAI PENDIDIKAN KEPRIBADIAN GENERASI MUDA DALAM KITAB AL-BARZANJI KARYA JA’FAR BIN HASAN - Makenun, Lukluil (IAIN Salatiga, 2009)
This research is to know (1) How is the systematic writing the book Al-Barzanji? (2) What educational value personality in the book Al-Barzanji, and (3) how the relevance of educational values of personality in the book Al-Barzanji with modern life today? It is a kind of library research. The results showed that the book Al-Barzanji contains prayers of adoration and the telling of the history of the Prophet Muhammad commonly sung to the rhythm or tone. Al-Barzanji book tells about the life of Prophet Muhammad SAW i.e. genealogy, childhood, adolescence, adulthood, until he was appointed to be an apostle. It also tells of the properties owned by the noble Prophet Muhammad as well as various events to be used as an example of humanity. While the educational values of personality contained in the book is the patience to face trials, trust, tawadhu, simplicity, forgiveness, deliberation, cherish and love the weak. Education Relevance personality in the book Al-Barzanji have the appropriate suitability with personality education required by today's youth, both in educational value and educational purposes personality. If the educational value of personality in the book Al-Barzanji exemplified or taught to students, it will produce the young generation that is virtuous and lift this nation as a nation which Berzanjen reading of the al-Barzanji together constitute a very popular tradition. The activity is part of the repertoire of the typical boarding vibrant literary sustainable long ago and persisted until today.